PERANCANGAN SISTEM PERAWATAN PULVERIZER MODEL MVM31F MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DI PT. XYZ - Hendarti, Devina Rosa (Universitas Nusa Putra, 2024)
The continuous increase in population growth leads to a rising demand for electrical energy. PT. XYZ as a supplier of electrical energy, relies heavily on the reliability of its components to meet this demand. The frequency of failures in pulverizer machines is one of the factors that reduce production capacity. This study uses the FMEA method combined with LTA to determine the failure consequences caused by failure modes, resulting in appropriate maintenance actions for critical components. From the FMEA analysis, 10 failure modes were identified along with their causes and effects if failures occur. Based on the RPN value calculations, a critical value of 69.2 was obtained. Components with RPN values above the critical value that need prioritized maintenance are the classifier and grinding roller. In the maintenance planning stage, 7 failure modes are placed under time-directed (TD) maintenance, 2 failure modes under condition-directed (CD) maintenance, and 1 failure mode under finding failure (FF) maintenance.